Literary Translation as Semiotic Interpretation in the Light of Philological Hermeneutics - Hambardzumyan, Diana (Armenian Folia Anglistika, 2005)
In recent years translation and particularly the translation of literature is perceived as interpretation. Several decades ago, Roman Jacobson put forward the idea of translation as semiotic interpretation distinguishing between in intralingual, interlingual and intersemiotic translations. While intralingual translation is the translation of verbal signs with the help of other signs, and inter-lingual translation is the interpretation of the verbal signs of one language with those of another language, intersemiotic translation is the interpretation of the verbal signs by means of non-verbal sign systems. Hence, according to the rule of extralinguistic signs, the main concern of the one who studies a piece of translation is the examination of the extralinguistic phenomena which have ensured the existence of the overall vertical context. The semiotic study of the original and the translation insists on revealing the vertical context, i.e. the literary, aesthetic, moral values and their recreation in the translated version with the help of the non-verbal signs of another language.